The developing Common Market : the structure of the EEC in theory and in practice - Paxton, John.; Walsh, A. E. (Boulder, Colo. : Westview Press, 1976)
The book is on the evolution of the Common Market, covering the era of the Treaty of Rome. The treaty provides for complete economic union so that goods, people and capital could pass over national boundaries of member countries.
Rev. ed. of Into Europe, by A. E. Walsh and J. Paxton.
Includes index.
Bibliography: p. 230-232.
osc 25/10/2018
Loans
Keywords: Common Markets